The Trypanosomatids Cell Cycle: A Brief Report - Passos, Arthur de Oliveira [UNESP]; Assis, Luiz H. C. [UNESP]; Ferri, Yete G. [UNESP]; Silva, Vitor L. da [UNESP]; Silva, Marcelo S. da [UNESP]; Cano, Maria Isabel N. [UNESP] (Springer Nature, 2022)
Trypanosomatids are protozoan parasites among which are the etiologic agents of various infectious diseases in humans, such as Trypanosoma cruzi (causative agent of Chagas disease), Trypanosoma brucei (causative agent of sleeping sickness), and species of the genus Leishmania (causative agents of leishmaniases). The cell cycle in these organisms presents a sequence of events conserved throughout evolution. However, these parasites also have unique characteristics that confer some peculiarities related to the cell cycle phases. This review compares general and peculiar aspects of the cell cycle in the replicative forms of trypanosomatids. Moreover, a brief discussion about the possible cross-talk between telomeres and the cell cycle is presented. Finally, we intend to open a discussion on how a profound understanding of the cell cycle would facilitate the search for potential targets for developing antiparasitic therapies that could help millions of people worldwide.
Keywords: Cell cycle phases; DNA replication; Organelle segregation; Synchronization; Telomere maintenance; Trypanosomatids